Lupus, Silica, and Dietary Omega-3 Fatty Acid Interventions. (December 2019) - Wierenga, Kathryn A.; Harkema, Jack R.; Pestka, James J.
Two environmental factors, crystalline silica (cSiO2 ), a toxic airborne particle encountered occupationally, and docosahexaenoic acid (DHA), a dietary omega-3 highly unsaturated fatty acid (HUFA), have the potential to influence the development of systemic lupus erythematosus (lupus). Using the NZBWF1 mouse, which spontaneously develops lupus, we found that intranasal exposure to cSiO2 significantly decreases latency and promotes rapid progression of the disease. Specifically, cSiO2 induces the development of ectopic lymphoid structures (ELS) containing germinal centers in the lungs that yield vigorous and diverse autoantibody responses locally and systemically. Transcriptomic analysis revealed that cSiO2 promotes a robust type I interferon gene signature that likely precipitates ELS neogenesis. Intriguingly, dietary supplementation with human-relevant doses of DHA impedes cSiO2 -induced gene expression, ELS neogenesis, autoantibody elevation, and glomerulonephritis in this lupus-prone mouse model. Together, our findings point to the feasibility of enhancing tissue omega-3 HUFAs as a personalized nutritional intervention to impede onset and progression of environment-triggered autoimmune disease.